2021
DOI: 10.1093/mnras/stab1826
|View full text |Cite
|
Sign up to set email alerts
|

From downtown to the outskirts: a radio survey of the Orion Nebula Cluster

Abstract: We present a newly enlarged census of the compact radio population towards the Orion Nebula Cluster (ONC) using high-sensitivity continuum maps (3–10 μJy bm−1) from a total of ∼30 h centimeter-wavelength observations over an area of ∼20′ × 20′ obtained in the C-band (4−8 GHz) with the Karl G. Jansky Very Large Array (VLA) in its high-resolution A-configuration. We thus complement our previous deep survey of the innermost areas of the ONC, now covering the field of view of the Chandra Orion Ultra-deep Project (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Nonetheless, in recent years there have been important detections of proplyds in lower EUV environments. Proplyds can be found in the ONC at separations of up to ∼ 1 pc from θ 1 C [20,110,111]. Meanwhile, [112] found proplyds in the vicinity of the B1V star 42 Ori in NGC 1977, demonstrating that B stars can drive external photoevaporative winds.…”
Section: Where and What Kind Of Proplyds Have Been Detected?mentioning
confidence: 98%
“…Nonetheless, in recent years there have been important detections of proplyds in lower EUV environments. Proplyds can be found in the ONC at separations of up to ∼ 1 pc from θ 1 C [20,110,111]. Meanwhile, [112] found proplyds in the vicinity of the B1V star 42 Ori in NGC 1977, demonstrating that B stars can drive external photoevaporative winds.…”
Section: Where and What Kind Of Proplyds Have Been Detected?mentioning
confidence: 98%
“…Compact radio sources have been found to be related to HII regions. The best-known and closest case is the Orion Nebula Cluster (ONC), where around 600 compact radio sources are found in the HII region ionized by the Trapezium stars (Forbrich et al 2016;Vargas-González et al 2021). As first suggested by Garay et al (1987); Garay (1987), most of these fall into two broad categories: first, sources with thermal radio emission from circumstellar matter, often protoplanetary disks ("Proplyds"), which are photo-evaporated in the intense UV field of the brightest Trapezium star θ 1 Ori C (O7Vp); second, nonthermal sources associated with the coronal activity of magnetically active low-mass members of the ONC, many of which also show X-ray emission and are (highly) variable (Forbrich et al 2021;Dzib et al 2021).…”
Section: Hii Region Candidatesmentioning
confidence: 99%
“…Even after applying additional spatial filtering, this often remains as uneven noise with occasional spurious point-like emission, and therefore automated source extraction methods typically require significant manual intervention to deal with artifacts. We thus searched for compact sources by visual inspection of the concatenated image followed by an automatic search only on the position of known X-ray sources in the Chandra Orion Ultra-deep Project (COUP; Getman et al 2005b), known sources detected at cm-wavelengths with the VLA reported by Forbrich et al (2016) and Vargas-González et al (2021), and millimeter sources reported in Friedel & Widicus Weaver (2011), Eisner et al (2016), andOtter et al (2021). These catalogues provide an updated and well characterized sample of X-ray and radio sources likely tracing the young stellar population in the Orion BN/KL region.…”
Section: Source Detectionmentioning
confidence: 99%
“…Centimeter radio emission from Young Stellar Objects (YSOs) has been explored in more detail in the last few years due to the improved sensitivity of radio facilities such as the Karl G. Jansky Very Large Array (VLA) and the Very Long Baseline Array (VLBA) (Rivilla et al 2015;Forbrich et al 2016;Sheehan et al 2016;Tobin et al 2016;Forbrich et al 2021;Vargas-González et al 2021). Recent analysis of deep VLA observations at cm-wavelengths towards hundreds of YSOs in the Orion Nebula Cluster (ONC) revealed intense radio flares with changes in flux density by a factor of 10 in less than 30 min and denominated as extreme radio variability events (Forbrich et al 2017, see also Vargas-González et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation